-6x-10=-82

Simple and best practice solution for -6x-10=-82 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6x-10=-82 equation:



-6x-10=-82
We move all terms to the left:
-6x-10-(-82)=0
We add all the numbers together, and all the variables
-6x+72=0
We move all terms containing x to the left, all other terms to the right
-6x=-72
x=-72/-6
x=+12

See similar equations:

| 2(13/5+x)=0 | | 1/4(x+6/1)=4/1 | | 18-6a=4a-4(a | | 6x+2=4x–20 | | 2x​​+7=9-8x(x) | | 6h+10=-10-1h+3h | | 4×c=24+c | | 20+y=-80 | | 2x​​+7=9-8(x) | | 19.9=d+7 | | -2x=-4-3x | | 2^(2x+1)-9*(2x)+4=0 | | 2x​​+7=9-8x | | -17(b-25)=-17+3(b+34) | | m+8.82=11.22 | | (2y-5)^2=0 | | 1/5x(1/5)=6/3(5/1) | | 10+5k=-2+8k | | 6x2-21x+15=0 | | s-1=1 | | -2(n+7)=14 | | p/8=p/9 | | 2^(2x+1)-9(2x)+4=0 | | 7u=9-10u=-18 | | 2x2+2x−4=0 | | 7.9p-5.9p=-4.9+15.7 | | 4x-3=2+38 | | 16=6-2k | | 2x+x=3690 | | -19x-43=56-x | | 0.25x+20=31 | | 25=5(c-5) |

Equations solver categories